PENGARUH MEDIA WORDWALL TERHADAP HASIL BELAJAR KOGNITIF PADA PEMBELAJARAN MATEMATIKA SEKOLAH DASAR - Salfa Tria Safitri; Nurpratiwiningsih , Laelia; Toharudin, Moh (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the effect of using Wordwall media on cognitive learning outcomes in elementary school mathematics instruction. The research employed a quantitative approach using a true experimental design with a posttest-only control group design. The study involved all fourth-grade students at SD Negeri Kalinyamat Kulon 01 and SD Negeri Margadana 04. A saturated sampling technique was applied, resulting in a total of 56 students participating in the study—28 students from SD Negeri Kalinyamat Kulon 01 as the experimental group and 28 students from SD Negeri Margadana 04 as the control group. Data collection instruments included multiple-choice questions to assess cognitive learning outcomes, and a self-assessment questionnaire was used to evaluate student engagement. The results showed that the t-test yielded a significance value of 0.012 (p < 0.05), indicating that the null hypothesis (Ho) is rejected and the alternative hypothesis (Ha) is accepted. This means that the use of Wordwall as a learning medium has a significant effect on students' cognitive learning outcomes in mathematics.